THE IMPACT OF PREECLAMPSIA ON MATERNAL MORTALITY IN ASIA: A COMPREHENSIVE EVIDENCE SYNTHESIS - Pratiwi Ramlan; Sunandar Said; Zulkarnain Sulaiman; Khaeriyah Adri; Mardhatillah; Devy Febrianti; Ruslang (RADJA PUBLIKA, 2025)
Preeclampsia remains one of the leading causes of maternal mortality globally, particularly in developing countries with limited access to antenatal care and emergency obstetric services. This study aims to synthesize scientific evidence regarding the relationship between preeclampsia and maternal mortality in Asia through a Systematic Literature Review (SLR). Using reputable databases such as Scopus, PubMed, and Web of Science, the study analyzed relevant articles published between 2020 and 2024. The results indicate that preeclampsia significantly contributes to maternal death through complications such as eclampsia, HELLP syndrome, and multi-organ failure. The trend of publications shows fluctuating research interest, with a peak in 2023, reflecting increased attention to maternal health post-pandemic. The majority of studies originate from the health sciences and biomedical fields, focusing on clinical interventions and pathophysiology. However, contributions from social, cultural, and policy-oriented research remain minimal, indicating a need for interdisciplinary integration. This review highlights critical risk factors such as chronic hypertension, limited prenatal care, and socio-economic disparities that exacerbate the impact of preeclampsia. It also emphasizes the importance of early detection, risk communication, and context-specific interventions in reducing maternal mortality. Ultimately, this synthesis provides a foundation for improving health policies, clinical practices, and future research directions related to preeclampsia and maternal mortality in Asia.